Estimation of electricity storage capacity of compact SMESs composed of stacks of Si-wafers loaded with superconducting thin film coils in spiral trenches formed by MEMS process. (September 2019) - Ichiki, Y; Ichiki, A; Hioki, T; Sasaki, M; Noh, J-H; Takai, O; Honma, H; Motohiro, T
Abstract: A method to estimate the electricity storage capacity of our compact superconducting magnetic energy storage system composed of stacks of Si-wafers loaded with superconducting thin film coils in spiral trenches formed by MEMS process was developed and tested for initial 6 designs of wafer coils. The results show energy storage density as low as around 6 Wh/ℓ. This is not caused by the limitation of the hoop stress but by the limitation of the maximum magnetic flux density. Further calculations for optimum wafer coil designs will be continued in which the effect of the maximum magnetic flux energy and the effect of the maximum hoop stress on the limit of the amount of the electrical energy storage come into a good balance.